BAP1 Immunohistochemistry and p16 FISH to Separate Benign From Malignant Mesothelial Proliferations. (July 2015) - Sheffield, Brandon S.; Hwang, Harry C.; Lee, Anna F.; Thompson, Kim; Rodriguez, Stephanie; Tse, Christopher H.; Gown, Allen M.; Churg, Andrew
Abstract : A variety of immunohistochemical (IHC) stains have been proposed to mark either benign or malignant mesothelial proliferations. Loss of the p16 tumor suppressor ( CDKN2A ), through homozygous deletions of 9p21, is a good marker of mesotheliomas but lacks sensitivity. Recent reports indicate that some mesotheliomas are associated with loss of BRCA-associated protein 1 ( BAP1 ) expression. Here we investigate BAP1 and p16 as potential markers of malignancy and compare test characteristics with previously proposed markers using a well-characterized tissue microarray. BAP1 protein expression was interrogated by IHC. The p16 locus was examined by fluorescence in situ hybridization (FISH) directed toward chromosome 9p21. Loss of BAP1 was identified in 7/26 mesotheliomas and 0/49 benign proliferations. Loss of p16 was identified in 14/27 mesotheliomas and 0/40 benign proliferations, yielding 100% specificity and positive predictive value for each marker. Together, BAP1 IHC and p16 FISH were 58% sensitive for detecting malignancy. Various combinations of p53, EMA, IMP3, and GLUT1 showed reasonably high specificity (96% to 98%) but poor to extremely poor sensitivity. Combined BAP1 IHC/p16 FISH testing is a highly specific method of diagnosing malignant mesotheliomas when the question is whether a mesothelial proliferation is benign or malignant and is particularly useful when tissue invasion by mesothelial cells cannot be demonstrated. However, combined BAP1/p16 FISH testing is not highly sensitive, and negative results do not rule out a mesothelioma. The test characteristics of previously proposed markers EMA, p53, GLUT1, IMP3 suggest that, even in combination, these markers are not useful tools in this clinical setting.